Fabrication of ultra-small monolayer graphene quantum dots by pyrolysis of trisodium citrate for fluorescent cell imaging - Hong GL; Zhao HL; Deng HH; Yang HJ; Peng HP; Liu YH; Chen W (International Journal of Nanomedicine, 2018)
Guo-Lin Hong,1 Hai-Ling Zhao,2,3 Hao-Hua Deng,3 Hui-Jing Yang,4 Hua-Ping Peng,3 Yin-Huan Liu,5 Wei Chen3 1Department of Laboratory Medicine, The First Affiliated Hospital of Xiamen University, Xiamen 361003, People’s Republic of China; 2School of Public Health, Xiamen University, Xiamen 361102, People’s Republic of China; 3Department of Pharmaceutical Analysis, Higher Educational Key Laboratory for Nano Biomedical Technology of Fujian Province, Fujian Medical University, Fuzhou 350004, People’s Republic of China; 4Department of Laboratory Medicine, Fujian Medical University, Fuzhou 350004, People’s Republic of China; 5Department of Laboratory Medicine, The Affiliated Fuzhou Second Hospital of Xiamen University, Fuzhou 350007, People’s Republic of China Background: The preparation and biological applications of ultra-small graphene quantum dots (GQDs) with accurate-controlled size are of great significance. Methods: Here in, we report a novel procedure involving pyrolysis of trisodium citrate and subsequent ultrafiltration for fabricating monolayer GQDs with ultra-small lateral size (1.3±0.5 nm). Results: The GQDs exhibit blue photoluminescence with peak position independent of excitation wavelength. The quantum yield of GQDs is measured to be 3.6%, and the average fluorescence lifetime is 2.78 ns. Conclusion: Because of high stability and low toxicity, GQDs are demonstrated to be excellent bioimaging agents. The ultra-small GQDs can not only distribute in the cytoplasm but also penetrate into the nuclei. We ensure that this work will add a new dimension to the application of graphene materials for nanomedicine. Keywords: graphene quantum dots, fluorescence, cell imaging, trisodium citrate, pyrolysis